PENGARUH PRODUCT, PRICE, PLACE, PROMOTION, DAN PHYSICAL EVIDENCE TERHADAP KEPUTUSAN PEMBELIAN - Haryana Sapta Widada (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
This study aimed to analyze the influence of Product, Price, Place, Promotion, and Physical Evidence on the consumers’ buying interest and Personal Factors as an intervening variable. The sampling technique used was simple random sampling that the sampling process in which every person has the same opportunity as others to be elected as members of the sample. taken as many as 55 respondents of the walking guest in Cakra Kusuma Yogyakarta Hotels. The analysis technique used is the test using SPSS version 17. It also performed classical assumption which include normality test, multicollinearity and heteroscedasticity test. Results of this study showed that the significant effect of Product on Personal Factors, Price, Place, Promotion, and Physical Evidence have a significant effect on Personal Factors. Product, Price, Place, Promotion, Physical Evidence, and Personal Factors are jointly significant effect on performance, both directly and indirectly through job satisfaction. On the basis of these results, management is advised, including to add western food menu, discounting, transportation agencies, the hotel layout, and give a touch of uniqueness, doing training for laundry division of and administration division. Keywords: Promotion, Physical Evidence, Buying Interest, Personal Factors.